SARS-CoV-2 inhibits induction of the MHC class I pathway by targeting the STAT1-IRF1-NLRC5 axis - Yoo, Ji-Seung; Sasaki, Michihito; Cho, Steven X.; Kasuga, Yusuke; Zhu, Baohui; Ouda, Ryota; Orba, Yasuko; de Figueiredo, Paul; Sawa, Hirofumi; Kobayashi, Koichi S. (Nature communications, 2021)
The MHC class I-mediated antigen presentation pathway plays a critical role in antiviral immunity. Here we show that the MHC class I pathway is targeted by SARS-CoV-2. Analysis of the gene expression profile from COVID-19 patients as well as SARS-CoV-2 infected epithelial cell lines reveals that the induction of the MHC class I pathway is inhibited by SARS-CoV-2 infection. We show that NLRC5, an MHC class I transactivator, is suppressed both transcriptionally and functionally by the SARS-CoV-2 ORF6 protein, providing a mechanistic link. SARS-CoV-2 ORF6 hampers type II interferon-mediated STAT1 signaling, resulting in diminished upregulation of NLRC5 and IRF1 gene expression. Moreover, SARS-CoV-2 ORF6 inhibits NLRC5 function via blocking karyopherin complex-dependent nuclear import of NLRC5. Collectively, our study uncovers an immune evasion mechanism of SARS-CoV-2 that targets the function of key MHC class I transcriptional regulators, STAT1-IRF1-NLRC5. The presentation of viral antigens to T cells via the MHC molecules is a critical component of the host response to viral infection. Here the authors suggest SARS-CoV-2 possesses the immune evasion strategy against the MHC class I pathway by targeting key transcriptional regulators.